2016
DOI: 10.1037/xhp0000257
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of local and global contributions to detection of shape with age.

Abstract: Radial Frequency (RF) patterns are a useful stimulus for assessing sensitivity to changes in shape. With these patterns it is possible to separate sensitivity to local curvature information from the ability to globally integrate information around the contour. Previous work has demonstrated that young, school-age children are less sensitive to deformation in RF patterns than adults. However, since the efficiency of contour integration was not assessed, age-related differences in performance could arise from ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 53 publications
(115 reference statements)
2
18
0
Order By: Relevance
“…Furthermore, there was no evidence of psychometric slopes becoming more shallow with increasing numbers of cycles of modulation (see Figures 8 and 9), a key feature of the SDT probability summation model (Baldwin et al, 2016;Pelli, 1985). In fact, previous research examining the effect of increasing numbers of cycles of modulation on psychometric functions have also found no evidence for a decrease in the slope of the psychometric functions (Baldwin et al, 2016;Cribb, Badcock, Maybery, & Badcock, 2016), further evidence against SDT probability summation for low frequency RF patterns which again, does not rely on summation estimates.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, there was no evidence of psychometric slopes becoming more shallow with increasing numbers of cycles of modulation (see Figures 8 and 9), a key feature of the SDT probability summation model (Baldwin et al, 2016;Pelli, 1985). In fact, previous research examining the effect of increasing numbers of cycles of modulation on psychometric functions have also found no evidence for a decrease in the slope of the psychometric functions (Baldwin et al, 2016;Cribb, Badcock, Maybery, & Badcock, 2016), further evidence against SDT probability summation for low frequency RF patterns which again, does not rely on summation estimates.…”
Section: Discussionmentioning
confidence: 77%
“…We predict, therefore, that suprathreshold amplitude RF patterns will be hard to find among rectified RF patterns with the same period and vice versa but, given their demonstrably global processing (Cribb et al, 2016;Dickinson et al, 2012;Green et al, 2017b;Hess et al, 1999;Loffler & Wilson, 2001;Schmidtmann et al, 2012;Tan et al, 2015), RF patterns should be rapidly identified among RF patterns with differing frequency by virtue of the shape cue. Further, RF patterns should be easy to find among circles because of the points of maximum curvature (and concomitant shape cue) they contain, but circles should be hard to find among RF patterns because the absence of these features when the circle is presented among a field of distractors containing them.…”
Section: Rf Patternsmentioning
confidence: 95%
“…In part, the RF pattern's utility in the study of visual processes arises from a demonstrable integration of shape information around the pattern (Bell & Badcock, 2008;Cribb, Badcock, Maybery, & Badcock, 2016;Dickinson, Han, Bell, & Badcock, 2010;Dickinson, McGinty, Webster, & Badcock, 2012;Green, Dickinson, & Badcock, 2017a, 2017bHess, Wang, & Dakin, 1999;Loffler et al, 2003;Schmidtmann, Kennedy, Orbach, & Loffler, 2012;Tan, Bowden, Dickinson, & Badcock, 2015). When cycles of modulation of a particular frequency are incrementally added to a pattern (with the remainder of the pattern completed by a circular arc) the threshold for discriminating a modulated pattern from a circle decreases at a rate that cannot be accounted for by probability summation-the increase in the probability of detection of single cycles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of channels included (Q) in estimates of probability summation under SDT have a large effect on the resulting predicted strength of integration. Previous research by Cribb, Badcock, Maybery, and Badcock (2016) has used both a ''low'' and ''high'' number of channels to provide an ultra-conservative estimate (low number of channels; Q ¼ 3; and consistent with Baldwin et al, 2016) and a more theoretically appropriate estimate (high number of channels; Q ¼ 120). The same method will be employed by the current study.…”
Section: Methodsmentioning
confidence: 99%